Elementary School Students' Writing Skills In Learning Indonesian Language Using Outdoor Learning Method - Hasanah, Tria Uswatun; Sunardi; Suparti (Journal of Classroom Action Research, 2025)
Writing skills are an indirect communication activity in the form of activities to express ideas, thoughts, and feelings in written form by paying attention to three basic components, opening, content, closing which must go through a regular practice process. Writing skills are important for students as a foundation in learning Indonesian and other subjects at the school level above. However, the facts in the field show that students' writing skills are still low. Students often study the science of types of writing and grammar, but they lack practice in writing short stories. For this reason, an outdoor learning method was tried to improve writing skills in grade IV elementary school students. Learning was carried out for three meetings at three different schools. The implementation began by providing a writing skills questionnaire (pre-test) and after the completion of the third meeting, students were given writing skills questionnaire questions (post-test) to measure the achievement of students' writing skills. The learning process uses the syntax of the outdoor learning method. The results of the study showed that students' writing skills improved after participating in learning. Students were able to create stories according to ideas, the content of the stories produced was well organized, the grammar used met the writing procedures, the language structure was well structured, the use of good and correct spelling and writing.